A dual‐band superconducting filter with a large bandwidth ratio. Issue 3 (27th November 2019) - Lu, Xinxiang; Guo, Xubo; Ma, Pengyu; Luo, Chenjie; Wei, Bin; Cao, Bisong
Abstract: In this study, we propose a stepped‐impedance‐stub loaded interdigital capacitor resonator for design of a dual‐band band‐pass filter with a large bandwidth ratio. The presented resonator has strong and weak couplings in the upper passbands (UPs) and lower passbands (LPs), respectively, so as to form a large upper/lower bandwidth ratio. Adopting a dual‐branch phase‐matched feedline structure can meet the external quality factors required for the UP/LP. Therefore, these two passbands, defined by their respective center frequencies and bandwidths, can be manipulated independently. A four‐pole dual‐band example filter with a lower bandwidth of 20 MHz at 1576 MHz and an upper bandwidth of 200 MHz at 2450 MHz is successfully designed on an YBCO/MgO superconducting wafer. The filter exhibits excellent frequency responses. The upper/LPs show insertion losses below 0.07/0.22 dB and return losses above 15.3/15.3 dB. The stopband rejection is better than 57 dB until the first spurious passband up to 6150 MHz (3.9 f L ).